PROBLEMS OF THE MEMORY AND EUROPEAN IDENTITY IN THE INHERITANCE OF THE ST. JOHN PAUL II - Ломака, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
This article analyzes the creative legacy of Pope John Paul II, where the light of Christian philosophy, history, Catholic teaching and my own experience, Pope ponders the roots of the existence of evil in the twentieth century. and in the modern Western world, considers the concept of political and historical memory of the nation, homeland, national identity, patriotism, social values, freedoms and modern democracy. Referring to the works of the great Pope know his thoughts with deep religious aspect, but also contain a lot of everyday, secular, close to the concerns of the person who is looking for its place in the modern world.